Effect of sodium hypochlorite in ground fluorotic enamel : shear bond strength and surface analysis = Efecto del hipoclorito de sodio en esmalte fluorótico tallado : resistencia adhesiva al cizallamiento y análisis de la superficie - Roque Márquez, José Gilberto
Evaluate the effect on the shear bond strength (SBS) of 5% NaOCl applied after acid etching on ground anterior teeth with fluorosis and analyze the surface with scanning electron microscopy (SEM), also compare fluorotic and healthy ground enamel by atomic force microscopy (AFM) and Vickers microhardness (VM). For the SBS test 30 anterior teeth with moderate and severe fluorosis according Dean index were selected by an examiner previously calibrated with an expert in fluorosis by using the intraclass correlation coefficient (ICC). With the help of a calibrated high speed diamond bur for veneer preparation and a parallel chamfer high speed diamond bur the vestibular face was prepared with a uniform reduction of .3 mm under water cooling. In one half of the vestibular face of the teeth the conventional adhesive procedure was carried out while in the other half was added an additional step with 5% NaOCl applied for 1 minute and washing after acid etchant. A resin post was adhered in each half and load was applied until fracture. The failure mode was evaluated and a SEM analysis was made. Posteriorly 10 samples of fluorotic and healthy ground enamel were used to measure the nanostructural characteristics by AFM (roughness average and absolute depth profile) and the VM in three operative steps (after ground, after etchant and after deproteinization). The Shapiro-Wilks and Brown-Forsythe methods were used to test the distribution of variables. The Paired Student's t-test was used to compare the differences between mean bond strength (MPa) in the two groups for SBS test. Chi-square analyzes were performed to compare the failure modes between groups. One-way ANOVA analysis and Tukey-Kramer post hoc test were used to compare groups for roughness average, absolute depth profile and Vickers microhardness. A greater SBS (32.17±4.20 MPa) and a surface more homogeneous and less contaminated were observed in the deproteinization subgruoup compared to the conventional...